1, 2, 4‐Triazine Chemistry Part IV: Synthesis and Chemical Behavior of 3‐Functionalized 5, 6‐Diphenyl‐1, 2, 4‐triazines towards Some Nucleophilic and Electrophilic Reagents. (16th December 2014) - Abdel‐Rahman, Reda M.; Makki, Mohamed S. T.; Ali, Tarik E.; Ibrahim, Magdy A.
Abstract : The synthesis and chemical behavior of 3‐functionalized 5, 6‐diphenyl‐1, 2, 4‐triazines towards some electrophilic andnucleophilic reagents are reviewed. The synthesis, unique features, and medicinal, pharmacological, and biological significance of these constituents are also reported. Abstract :